2009
DOI: 10.1016/j.febslet.2009.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric structure of LOV domains in Arabidopsis phototropin

Abstract: a b s t r a c tOligomeric structures of the four LOV domains in Arabidopsis phototropin1 (phot1) and 2 (phot2) were studied using crosslinking. Both LOV1 domains of phot1 and phot2 form a dimer independently on the light conditions, suggesting that the LOV1 domain can be a stable dimerization site of phot in vivo. In contrast, phot1-LOV2 is in a monomer-dimer equilibrium and phot2-LOV2 exists as a monomer in the dark. Blue light-induced a slight increase in the monomer population in phot1-LOV2, suggesting a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 23 publications
1
32
1
1
Order By: Relevance
“…This fact suggests that LOV1 domains of angiosperm LLPs may have lacked the cysteine during their evolution. The LOV1 domains of A. thaliana phototropin 1 and 2 are proposed to function as a dimerization site for the phototropins (26). Interestingly, the dimer formation is light-independent (26).…”
Section: Discussionmentioning
confidence: 99%
“…This fact suggests that LOV1 domains of angiosperm LLPs may have lacked the cysteine during their evolution. The LOV1 domains of A. thaliana phototropin 1 and 2 are proposed to function as a dimerization site for the phototropins (26). Interestingly, the dimer formation is light-independent (26).…”
Section: Discussionmentioning
confidence: 99%
“…Dimerization of Phot1-The present SAXS evidence as well as the quaternary structures of LOV1 (15,16) and LOV2-J␣ (17) implies that full-length At phot1 probably exists as a dimer. However, the arrangement of the LOV1 dimer relative to the LOV2 dimer is still unknown.…”
Section: Arrangement Of the Functional Domains In P1l2lk-mentioning
confidence: 91%
“…In vitro transphosphorylation between glutathione S-transferase (GST)-tagged and non-GST-tagged versions of phot1 was also observed in insect cells using native ( Figure 10A) or constitutively active (see Supplemental Figure 8 online) forms of the receptor, further demonstrating that phot1 is capable of intermolecular phosphorylation. Isolated LOV1 domains of Arabidopsis phot1 form dimers and are proposed to function as sites of receptor dimerization (Nakasako et al, 2004(Nakasako et al, , 2008Katsura et al, 2009). However, we found that the LOV2K region of phot1 retains light-induced kinase activity when expressed in insect cells and is able to transphosphorylate phot1 D806N ( Figure 10B).…”
Section: Phot1 Internalization Is Promoted By Intermolecular Phosphormentioning
confidence: 99%
“…While LOV1 domains of phot1 form homodimers in vitro (Nakasako et al, 2004(Nakasako et al, , 2008Katsura et al, 2009), the ability of phot1 LOV2K to mediate intermolecular phosphorylation in vitro and in vivo indicates that this mechanism can occur in the absence of LOV1 (Figure 10). The LOV2 domain of phot1 is known to dimerize in solution depending on its concentration (Nakasako et al, 2004;Katsura et al, 2009). Studies are now aimed at defining the site(s) of receptor dimerization and to assess whether intermolecular phosphorylation is essential for phototropin signaling.…”
Section: Intermolecular Autophosphorylation Of Phot1 Is Not Dependentmentioning
confidence: 99%